Reframing Transnational Political Islam through Humanitarian Diplomacy: Gus Yahya, Islam Nusantara, and Indonesia’s Religious Soft Power - Firnanda, Rizky; Rasyadi, Imron; Adnan, Irfan Maulana; Diani, Fathya Shafa (Indonesian Journal of Interdisciplinary Islamic Studies (IJIIS), 2026)
Globalization has intensified the cross-border circulation of Islamic ideas, organizations, and political identities, creating both opportunities for cooperation and risks of polarization. This study examines how Gus Yahya reframes transnational political Islam through humanitarian diplomacy, Islam Nusantara, and Indonesia’s religious soft power. Using a qualitative interpretive design, the study applies Faircloughian critical discourse analysis to Gus Yahya’s speeches, writings, interviews, public statements, and institutional initiatives, including Religion 20 and Humanitarian Islam. The analysis identifies a consistent shift from ideological competition and the pursuit of political authority toward humanitarian ethics, plural citizenship, and peaceful coexistence. This reframing is organized through recurring concepts such as insaniyyah, ta‘awun, rahmah, justice, moderation, and rahmatan lil-‘alamin, which present Islam as a moral force for guiding political life without legitimizing domination. Islam Nusantara functions as the principal theological and cultural foundation of this strategy by connecting Islamic tradition with nationalism, local culture, pluralism, and global responsibility. Religion 20, interfaith partnerships, and Nahdlatul Ulama’s international networks also position religious diplomacy as networked soft power that expands representation, access, and narrative circulation. However, the findings do not establish measurable policy change or shifts in public attitudes, and the strategy remains constrained by elite-centered representation, contested meanings of moderation, institutional dependence, and the moderate–radical binary. The study contributes to scholarship on political Islam and religious diplomacy by showing how locally rooted Islamic discourse can generate a Global South model of humanitarian engagement while requiring careful distinction between symbolic influence and demonstrated diplomatic effectiveness.